The conformability of french listening skills learning materials in Frenchblabla Podcasts with the CEFR curriculum and the Kurikulum Merdeka - Nabilah Hendrayani; Tri Indri Hardini; Dante Darmawangsa (Inovasi Kurikulum, 2023)
The variety of emerging digital technology platforms for learning French, including the Podcast platform, continues to increase. These platforms allow users to be able to learn independently. Therefore, it is essential to study the material presented in the media. This study focuses on analyzing the suitability of the material on the frenchblabla podcast with the CEFR curriculum and the Merdeka curriculum in order to improve French listening skills for level A1. The study employs qualitative methods in the form of descriptive analysis. In this study, researchers identified learning French for level A1 through the Frenchblabla podcast. The results of the study show that the relevance of the material presented in this podcast meets all the CEFR-based entry-level competency indicators, which are spread across different podcast episodes. This study concluded that the Frenchblabla podcast provides content that fully complies with the European Standards for Learning Foreign Languages (CEFR) and also answers the demands of the Merdeka Indonesia Curriculum for beginner levels, especially A1-A2 levels. Furthermore, the material for this podcast conforms to the Merdeka curriculum structure for Stage F. Therefore, the alignment and arrangement of the material make this podcast media have great potential as a learning aid that can improve students' French listening skills. AbstrakBeragamnya kemunculan platform teknologi digital untuk pembelajaran bahasa Prancis terus meningkat, salah satunya adalah platform Podcast. Platform-platform ini memungkinkan pengguna untuk dapat belajar secara mandiri. Oleh karena itu, penelaahan materi yang disajikan dalam media tersebut menjadi penting untuk dilakukan. Penelitian ini berfokus pada analisis kesesuaian materi pada podcast Frenchblabla dengan kurikulum CEFR dan kurikulum Merdeka guna meningkatkan keterampilan menyimak bahasa Prancis untuk tingkat A1. Peneliti menggunakan metode kualitatif berupa analisis deskriptif. Dalam penelitian ini, peneliti mengidentifikasi pembelajaran bahasa perancis untuk level A1 melalui podcast Frenchblabla. Hasil penelitian menunjukan bahwa relevansi materi yang disajikan dalam podcast ini memenuhi semua indikator kompetensi tingkat pemula berbasis CEFR yang tersebar dalam episode podcast yang berbeda. Penelitian ini sampai pada kesimpulan bahwa podcast Frenchblabla menyajikan konten yang sepenuhnya sesuai dengan Standar Eropa untuk Pembelajaran Bahasa Asing (CEFR) dan juga menjawab tuntutan Kurikulum Merdeka Indonesia untuk tingkat pemula, khususnya tingkat A1-A2. Lebih lanjut, materi podcast ini sesuai dengan struktur kurikulum Merdeka untuk Tahap F. Oleh karena itu, keselarasan dan penataan materi tersebut menjadikan media podcast ini memiliki potensi besar sebagai alat bantu pembelajaran yang dapat meningkatkan keterampilan menyimak bahasa Prancis siswa.Kata Kunci: Keterampilan menyimak; kurikulum CEFR; Kurikulum Merdeka; materi pembelajaran bahasa Perancis; media pembelajaran; podcast